Comparison Of LCL Handling Charges At The Container Freight Station (CFS) Line 1 And Line 2 Depots - Prasasti, Naiya; Dahri, Muhammad; Yudianto, Prima Yudha; Rakhman, Rizqi Aini (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Less than Container Load (LCL) is defined as cargo whose volume does not fill a full container and its movement requires allocation of LCL handling charges. This study aims to conduct a comparative study of LCL handling charges between Line 1 Container Freight Station (CFS) facilities and Line 2 depot facilities. Differences in operational locations and customs status between Line 1 CFS and Line 2 depots are predicted to cause variations in cost structures that directly affect the efficiency of the logistics supply chain. This study has three main objectives: identifying LCL service procedures, analyzing the development of LCL throughput volume for the period 2021–2024, and comparing LCL handling charges between the two locations. The methodology used is quantitative with a descriptive approach. Data were obtained through observation, interviews, and document studies at the Commercial and Business Development Department. Data analysis involved calculating the Compound Annual Growth Rate (CAGR) to measure volume trends and descriptive comparative analysis to evaluate cost structures. The results show that LCL services are implemented through three main Job Orders: Receiving Service LCL (RSL), MIM, and Delivery Cargo. The LCL throughput trend shows a positive increase with a CAGR of 17.996%. Furthermore, the cost analysis results show that the Line 2 depot charges a higher LCL handling charge, which is around 26%–30% compared to the Line 1 CFS. Thus, the Line 1 CFS is proven to provide a competitive advantage for service users through a more efficient LCL charge handling structure.